2014
DOI: 10.7326/m13-0974
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Time Spent on Parenting and Domestic Responsibilities by High-Achieving Young Physician-Researchers

Abstract: Background Female physician-researchers do not achieve career success at the same rate as men. Differences in nonprofessional responsibilities may partially explain this gap. Objective To investigate the division of domestic labor by gender in a motivated group of early-career physician-researchers. Design Nationwide postal survey between 2010 and 2011. Setting United States. Participants Physician recipients of National Institutes of Health K08 or K23 awards between 2006 and 2009 with active academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
489
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 637 publications
(511 citation statements)
references
References 32 publications
16
489
1
5
Order By: Relevance
“…This may relate to the fact that women tend to have additional domestic and parenting responsibilities compared to their male counterparts. Research has demonstrated this to be the case for female versus male physicians [28], but the present data suggest that the differences may be apparent by the time of medical school. As a result, female medical students, in particular, may benefit from learning strategies to share household tasks more equitably with their partner and/or utilize organizational and time management strategies more effectively.…”
Section: Discussionmentioning
confidence: 49%
“…This may relate to the fact that women tend to have additional domestic and parenting responsibilities compared to their male counterparts. Research has demonstrated this to be the case for female versus male physicians [28], but the present data suggest that the differences may be apparent by the time of medical school. As a result, female medical students, in particular, may benefit from learning strategies to share household tasks more equitably with their partner and/or utilize organizational and time management strategies more effectively.…”
Section: Discussionmentioning
confidence: 49%
“…Potential interventions to address these barriers to promotion include greater investment in early research career development for women and modifying the promotions process in nonresearch career tracks. Alleviating sex differences in promotion from associate to full professor may require a distinct set of strategies.A number of explanations have been advanced to explain sex differences in faculty rank, [7][8][9][20][21][22][23][24] including explanations for why women faculty have lower average research productivity than men, 24 which may impede promotion, and explanations for why, even after accounting for research productivity, women are less likely than men to be full 22,25,26 childrearing, and different preferences on work-life balance 27,28 may contribute to sex differences in full professorship primarily by reducing research productivity but should have little independent effect on faculty rank once measures of productivity are accounted for. In contrast, women may face difficulties finding effective mentors and receiving recognition from senior colleagues, 7,20,21,29 workplace discrimination, and inequitable allocation of institutional resources.…”
mentioning
confidence: 99%
“…Our present study focuses on a sample of faculty highly focused on research careers, who have obtained awards that guarantee support to protect research time. We found that women in this population were more likely to have asked their supervisor for a reduction in clinical hours, suggesting that even though we currently observe no differences in the desire to decrease clinical hours (nor, as we have reported elsewhere, 30 do we currently observe large differences in clinical hours by gender at the time of the survey), women may have been asked to shoulder a greater clinical burden earlier in their careers. Alternatively, greater demands to perform domestic labor may limit the ability of women to expand their work hours to maintain research time when clinical demands are high.…”
Section: Discussionmentioning
confidence: 41%
“…As we have previously reported, female physicians from this same survey described spending 8.5 more hours per week on parenting and domestic tasks. 30 This may help to illuminate the gender difference observed here regarding negotiation to limit clinical time.…”
Section: Discussionmentioning
confidence: 99%